2020
DOI: 10.1038/s41467-020-18209-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable emergent patterns in active chiral fluids

Abstract: Active fluids comprised of autonomous spinning units injecting energy and angular momentum at the microscopic level represent a promising platform for active materials design. The complexity of the accessible dynamic states is expected to dramatically increase in the case of chiral active units. Here, we use shape anisotropy of colloidal particles to introduce chiral rollers with activity-controlled curvatures of their trajectories and spontaneous handedness of their motion. By controlling activity through var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 52 publications
(67 reference statements)
5
77
2
Order By: Relevance
“…In Biology, sperm [11,12], vinegar eels [13,14], and other microswimmers [15][16][17] synchronize the wriggling of their tails which is speculated to hydrodynamically couple to their motion. In Chemistry, magnetic Janus particles [18][19][20], dieletric Quinke rollers [21][22][23], and other active entities [24] lock their rotations enabling a kind of sync-dependent self-assembly. In Engineering, land-based robots and aerial drones can be programmed to swarm based on their synchronizable internal clocks [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In Biology, sperm [11,12], vinegar eels [13,14], and other microswimmers [15][16][17] synchronize the wriggling of their tails which is speculated to hydrodynamically couple to their motion. In Chemistry, magnetic Janus particles [18][19][20], dieletric Quinke rollers [21][22][23], and other active entities [24] lock their rotations enabling a kind of sync-dependent self-assembly. In Engineering, land-based robots and aerial drones can be programmed to swarm based on their synchronizable internal clocks [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Downsizing spinner chains is a challenge but might be achieved by appropriate new techniques. Rotating microparticles have been manufactured in various ways (16,24,26,45,46). Adding connectors between particles is possible in principle (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic behavior of active chiral fluids is highly complex. Most notably, active chiral fluids exhibit active turbulence (14), aster-like vortices and rotating flocks (15)(16)(17), odd viscosity in the bulk (8), and enhanced surface flow near surfaces and interfaces (18)(19)(20). Chiral fluids have been experimentally realized at different scales (7,12,(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…29 Recent studies of circle swimmers with short-range anisotropic interactions have revealed even more intriguing features. For example, simulations have demonstrated that chiral active particles with an asymmetric 24,30,31 or elongated 32 shape display vortex structures. Chiral active particles with chemotactic alignment can form a global traveling wave.…”
Section: Introductionmentioning
confidence: 99%